ISOLASI FLAVONOID DAN UJI BIO AKTIVITAS DARI TERUNG PIRUS (Cyphomandra betacea (Cav.) Sendtn) - ellizar, Ellizar; Maaruf, Yustini (Sainstek, 2009)
This research was a flavonoid isolation to determine the characteristics and the bioactivities of  the Cyphomandra betacea (Cav) Sendtn. Flavonoid was known as a compound which contribute to physiological and pharmacological values to human. The compound was found in angiospermae, gymnospermae, and pteridopita. The flavonoid was also presumed can be used as a dyer and to protect human as medicines. The method of isolation by using maceration with methanol, then was  fractionated by using n-hexane and ethyl acetate. Ethyl acetate fraction seperated column chromatography by silica-gel 60, treated n-hexane: ethyl acetate and ethyl acetate: methanol as eluen. The purity of fraction was identified by KLT and the melting point. Pure flavonoid (58.1 mg) as white yellow needle crystal obtained has the interval range melting point as much 168. 4 to 169.90C. The bioactivity test of the flavonoid shows that the flavonoid  function as  antibacteria, but not function as antifungy. The flavonoid was assumed as O-glycoside flavon with OH at C-5, C-3’, C-4’ and prenil at  C-6. Key words:     flavonoid, dye, isolation, bioactivity & antibakteria